ANALISA PENGARUH PENAMBAHAN LIMBAH KAYU JATI DAN SERABUT KELAPA SERTA GYPSUM PADA TANAH PANGGUNG JEPARA TERHADAP TINGKAT KEKUATAN GESER DAN PENGEMBANGAN TANAH - Arifuddin, Arfendi; Zulfa, Ivana; Budirahardjo, Slamet; Husodo, Ibnu Toto (Universitas PGRI Semarang, 2022)
AbstractThe soil in the Panggung Village area, Kedung District, Jepara Regency, was found to have signs of collapse and uneven ground and fractures occurred in structural bulkheads due to uneven and stable land subsidence. One of the factors causing the signs of failure, cracks and faults is triggered because most of the area has a type of soil with a low level of shear strength.In this study, an experiment was conducted on mixing the original soil with a mixture of added materials in the form of teak wood powder and coconut fibers and gypsum. The percentage of addition of added materials is 8%, 10% and 12% and 3% gypsum with two ratios of added materials (25% SKJ and 75% SKP) with a comparison (75% SKJ and 25% SKP) to determine the nature of the original soil after Added materials are added by testing physical properties and engineering properties.From the research that has been done, the percentage of addition of added material that shows the best soil characteristics is adjusted to the percentage of comparison, namely the highest specific gravity test from the addition of 8% in the comparison percentage (25% SKJ and 75% SKP), Atteberg limit test with the lowest plasticity index of the addition of 10 % in the comparison percentage (25% SKJ and 75% SKP), testing the lowest optimum proctor modified moisture content from the addition of 8% in the comparison percentage (25% SKJ and 75% SKP) with the maximum dry soil density from the addition of 8% in the comparison percentage (25% SKJ and 75% SKP), in the CBR test the highest CBR value occurred in the 8% addition test, the soil shear strength test used the highest soil cohesion value from the addition of 10% in the comparison percentage (75% SKJ and 25% SKP) and used an increase in the highest value of the shear angle of the soil in the addition of 8% on the percentage (75% SKJ and 25% SKP) , then testing the land development uses the smallest value that occurs in the addition of 8% in the comparison percentage (25% SKJ and 75% SKP).Â Keywords: Soil Waste, Soil Stabilization, Direct Shear, Swelling